Markov-modulated bernoulli-based performance analysis for gentle BLUE and BLUE algorithms under bursty and correlated traffic - Alsaaidah A.; Fadzli M.; Abdel-Jaber H.; Mohd Zalisham Jali (Science Publications, 2024)
Indexed by Scopus